Preservation of Local Wisdom: Analysis of Cultural Tourism Policy Implementation through Kasanga Festival in Denpasar City - Dhea Yulianingsih; Slamet Usman Ismanto; Candradewini Candradewini (Borong Newinera Publisher, 2024)
This research delves into the cultural preservation efforts in Denpasar City through the Kasanga Festival, initiated by the Department of Culture of Denpasar City in collaboration with Pasikian Yowana Kota Denpasar. As the provincial capital of Bali, Denpasar is home to diverse ethnic groups contributing to its cultural richness. The Kasanga Festival, first held in March 2023, is an initiative by the Department of Culture of Denpasar City in partnership with Pasikian Yowana Kota Denpasar. The festival aims to develop traditional art, cultural, and culinary skills among the youth, strengthen customary institutions, empower the younger generation, and enhance cultural tourism appeal. This study employs qualitative methods, including in-depth interviews, field observations, document analysis, and case studies, to gain comprehensive insights into the festival's implementation. The research findings indicate that the Kasanga Festival has successfully fostered cultural continuity, stimulated economic growth, and empowered the community. This study contributes valuable insights into cultural tourism and cultural preservation in Denpasar City.